UJI EFEKTIVITAS DISINFEKTAN YANG DIGUNAKAN UNTUK MEMBERSIHKAN LANTAI POLIKLINIK RSUP DR. M. DJAMIL PADANG TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS DAN ESCHERIACHIA COLI - Zulkarnain, Anugrah; Rasyid, Roslaili; Kurniawati, Yulia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Disinfection is one of the preventive program in preventing the growth of bacteria in hospitals such as Staphylococcus aureus and Escherichia coli which are bacteria that cause nosocomial infections, but the use of disinfectants as antibacterials must be in accordance with the right dose and frequency to prevent the development of antibacterial resistance (AMR). This study aims to determine the effectiveness of the disinfectant used to clean the polyclinic floor of RSUP Dr. M. DJamil Padang against Staphylococcus aureus and Escherichia coli. This type of research is an experiment with purposive sampling technique there samples obtained from the polyclinic of RSUP Dr. M. Djamil Padang as many as 20 samples. Sample analysis using Kirby-bauer method (diffusion disc) with 3 times (Triplo) against 2 types of bacteria, Staphylococcus aureus and Escherichia coli to determine the effectiveness of the inhibition of disinfectant. The results showed that the disinfectant used had different inhibitory values against Staphylococcus aureus and Escherichia coli bacteria. The disinfectant has a weak effectiveness against Staphylococcus aureus bacteria with an average diameter of inhibitory obtained of 13.21 mm with the highest value of 15.33 mm and the lowest value of 11.95 mm. The results showed that Escherichia coli bacteria were resistant to the disinfectant used, because there was no inhibitory activity produced by the disinfectant, so the use of the disinfectant was not very effective in inhibiting the growth of Escherichia coli bacteria. The conclusion of this study is the disinfectant used by RSUP Dr. M. Djamil Padang to clean the polyclinic floor has a sensitivity that is less effective in inhibiting the growth of Staphylococcus aureus bacteria, while Escherichia coli bacteria have significant resistance to this disinfectants. So it is recommended to RSUP Dr. M. Djamil Padang to review of the disinfectant used